2023
DOI: 10.3390/microorganisms11030554
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Toxic Activity of the Graphene Oxide in the Ex Vivo Model of Human PBMC Infection with Mycobacterium tuberculosis

Abstract: Graphene Oxide has been proposed as a potential adjuvant to develop improved anti-TB treatment, thanks to its activity in entrapping mycobacteria in the extracellular compartment limiting their entry in macrophages. Indeed, when administered together with linezolid, Graphene Oxide significantly enhanced bacterial killing due to the increased production of Reactive Oxygen Species. In this work, we evaluated Graphene Oxide toxicity and its anti-mycobacterial activity on human peripheral blood mononuclear cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We have recently demonstrated that GO exerts a generalized toxic effect on human PBMCs ( Salustri et al, 2023 ), hence we aimed to investigate whether GQDs have any toxicity in similar settings. We assessed cellular viability 1 h post treatment measuring 7AAD PC5.5-A signal (7AAD PC5.5-A binds DNA with high affinity and it is efficiently excluded by viable cells resulting an optimal marker for dead cells which have damaged nuclear membranes).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently demonstrated that GO exerts a generalized toxic effect on human PBMCs ( Salustri et al, 2023 ), hence we aimed to investigate whether GQDs have any toxicity in similar settings. We assessed cellular viability 1 h post treatment measuring 7AAD PC5.5-A signal (7AAD PC5.5-A binds DNA with high affinity and it is efficiently excluded by viable cells resulting an optimal marker for dead cells which have damaged nuclear membranes).…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that GO can entrap extracellular mycobacteria ( De Maio et al, 2019 ) and, depending on its surface-exposed functional groups, enhances the anti- Mtb activity of LZD, but not of INH and AMK ( De Maio et al, 2020 ). However, GO exerts a toxic effect on immune cells reducing monocytes viability and prompting an early activation of CD4 lymphocytes ( Salustri et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…191 Graphene oxide showed promising anti-TB potential by trapping mycobacteria, but it exhibited toxicity to human immune cells, impairing Mycobacterium tuberculosis clearance. 192 MoS 2 nanosheets (NSs) were found to activate the KLF4-signaling pathway in both in vitro 3D Caco-2 spheroids and in vivo mouse intestines. Exposure to MoS 2 NSs led to decreased body weight, altered organ coefficients, increased Mo elements, and morphological changes in intestines, including villi shortening and decreased crypt depth.…”
Section: Healthcare Applicationsmentioning
confidence: 99%
“…In C. elegans , it affected organ function, transcription factor nuclear accumulation, neuronal health, and antioxidant defense mechanisms . Graphene oxide showed promising anti-TB potential by trapping mycobacteria, but it exhibited toxicity to human immune cells, impairing Mycobacterium tuberculosis clearance . MoS 2 nanosheets (NSs) were found to activate the KLF4-signaling pathway in both in vitro 3D Caco-2 spheroids and in vivo mouse intestines.…”
Section: Properties Of 2d Nanomaterials Used In Healthcare Applicationsmentioning
confidence: 99%